CONVERGENCE OF SEQUENCES IN (3, j, ρ)-N-METRIZABLE SPACES, j ∈ 1, 2 - Dimovski, Tomi; Dimovski, Dončo (Matematichki Bilten, 2018)
In this paper we consider \((3,j,ρ)\)-N-metrizable spaces, \(j {1,2}\), in terms of convergence of sequences. We define four types of convergence in these spaces. We give examples which show that in general these four types of convergence are not equivalent in \((3,1,ρ)\)-N-metrizable spaces. We show that in \((3,2)\)-N-metrizable spaces these four types of convergence are equivalent.